2004
DOI: 10.1086/423992
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gas Cooling on the Shapes of Dark Matter Halos

Abstract: We analyze the effect of dissipation on the shapes of dark matter (DM) halos using high-resolution cosmological gasdynamics simulations of clusters and galaxies in the LCDM cosmology. We find that halos formed in simulations with gas cooling are significantly more spherical than corresponding halos formed in adiabatic simulations. Gas cooling results in an average increase of the principle axis ratios of halos by ~ 0.2-0.4 in the inner regions. The systematic difference decreases slowly with radius but persist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
400
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(433 citation statements)
references
References 43 publications
32
400
1
Order By: Relevance
“…In clusters, the dominant form of atomic matter is not stars, but hot gas. Gas cooling does not have a major effect on the profiles except close to the inner regions of the cluster, roughly r < 0.1R vir (Kazantzidis et al 2004;Duffy et al 2010;Cui et al 2011). Beyond this radius the gas distribution is determined by the self-consistent gravitational potential.…”
Section: Halos and Concentrationsmentioning
confidence: 93%
“…In clusters, the dominant form of atomic matter is not stars, but hot gas. Gas cooling does not have a major effect on the profiles except close to the inner regions of the cluster, roughly r < 0.1R vir (Kazantzidis et al 2004;Duffy et al 2010;Cui et al 2011). Beyond this radius the gas distribution is determined by the self-consistent gravitational potential.…”
Section: Halos and Concentrationsmentioning
confidence: 93%
“…Previous hydrodynamical numerical studies of galaxy formation have found that the cooling of baryons leads to significantly rounder halos (Dubinski 1994;Kazantzidis et al 2004;Springel et al 2004;, especially in the central regions where s can increase by as much as 0.2-0.3. At the moment it is unclear how much of this effect is due to a potential overcooling problem in these simulations.…”
Section: Host Halo Shapementioning
confidence: 96%
“…We have relied heavily on the hypothesis that the BCG is somewhat aligned with the dark matter in the galaxy cluster. Finally, we have drawn some loose conclusions about the efficacy of this approach in differentiating the predictions of CDM and the hydrodynamic simulations of [3], but we note that these are likely to be altered by the influence of baryons on substructure. We hope that future work will address these issues.…”
Section: Discussionmentioning
confidence: 93%
“…The conventional belief is that since the baryons are a small fraction of the total cluster mass, baryonic physics has a negligible effect on the halo shape out near the virial radius. However one group [3] has presented evidence to the contrary from numerical simulations of cluster formation which include gas cooling and feedback processes. They suggest that particle orbits are circularized by gravitational interaction with the deeper potential wells from baryonic cooling in the cluster's core, leading to an observable change in halo shape even at large radius.…”
Section: Introductionmentioning
confidence: 99%